STRATEGY FOR DEVELOPING GAYO ARABICA COFFEE PRODUCTS IN TAKENGON - Taufiqurrahman (CV. Radja Publika, 2025)
This study aims to analyze the development strategy of processed Gayo Arabica coffee products in Central Aceh and Bener Meriah Regencies as an effort to enhance the added value and competitiveness of this regional superior commodity. The research employed a descriptive quantitative method with data collected through observations, interviews, and surveys involving farmers and coffee industry actors. The analysis used the SWOT (Strengths, Weaknesses, Opportunities, Threats) approach combined with the IFE and EFE matrices to evaluate the internal and external conditions of the Gayo coffee industry. The results show that the strategic position of Gayo Arabica coffee lies in the Weakness–Opportunities (W–O) quadrant, indicating that development strategies should focus on utilizing external opportunities to overcome internal weaknesses. The main strengths are the distinctive flavor and aroma recognized globally, as well as institutional support such as cooperatives and international certifications (Fair Trade, Organic, and Geographical Indication). The primary weaknesses include limited processing technology, low human resource capacity, and restricted access to finance. The recommended strategies include improving post-harvest technology and human resource capacity, strengthening MSME and cooperative institutions, developing the “Gayo Specialty” brand, and utilizing digital marketing and coffee tourism. Implementing these strategies is expected to transform the Gayo coffee industry from a raw bean exporter into a high-value processed coffee industry with global competitiveness, thereby contributing to local community welfare and sustainable regional economic growth.